Rest for Your Souls? Religion, Meaning, and Purpose in Life, and Sleep Quality in the United States - Upenieks, Laura (Journal for the scientific study of religion, 2022)
Although vibrant interdisciplinary literature has extensively documented the importance of quality sleep for health and longevity, many Americans struggle with sleep disorders. One factor which has received far less research attention to date in predicting sleep quality is religion/spirituality. The current study uses nationally representative data from the 2017 Baylor Religion Survey to assess how three dimensions of religion/spirituality, including religious attendance, divine control (the belief in God's causal influence over daily life), and religious doubt (doubt in God's existence), associate with sleep quality. Given that very few population-based studies have formally tested any underlying mechanisms of the association between religion/spirituality and sleep, we also consider the potential mediating influence of the sense of meaning and purpose in life. Results suggest that greater religious attendance and divine control were associated with better sleep quality, while doubt in God's existence among religious believers was associated with lower sleep quality. The sense of meaning/purpose in life was found to mediate the relationship between religious attendance and divine control and sleep quality and confound the association between religious doubt and sleep quality. Taken together, our findings incorporate understudied measures of religion/spirituality and introduce the sense of meaning and purpose in life as a new mechanism.